Nonlinear dynamic behavior of simply-supported RC beams subjected to combined impact-blast loading. (15th February 2019) - Zhang, Chunwei; Gholipour, Gholamreza; Mousavi, Asma Alsadat
Highlights: The nonlinear dynamic responses and failure behaviors of simply supported RC beams subjected to a combination of impact and blast loadings are investigated. The beam suffers more spallation in its depth when the impact load is applied before than blast loading. The beam suffers more damages when the sequence blast loading initiates at the free vibration stage of response to impact load. The beam experience greater internal forces when the blast load initiates simultaneous with the first peak impact force. Abstract: Despite many studies existed in the literature on the investigation of reinforced concrete (RC) structures under impact or blast loads separately, this paper numerically evaluates the nonlinear dynamic responses and failure behaviors of simply-supported reinforced concrete (RC) beams subjected to the combination of impact and blast loads using LS-DYNA. The effects of the middle-rate impact loading stresses on the blast responses of RC beams are studied by considering different combined loading scenarios varied by the sequence of applying loads and the time lag between the initiations of these loads. From the simulation results, it was observed that when the impact load is applied on the beam prior to blast loading, it suffers a more severe spallation in the depth due to the flexural-shear stresses generated in the impacted beam before the initiation of the subsequent blast load. In addition, the beam suffers a more severe spallation in the depth and residual plastic deformations when the subsequent blast load initiates during the free vibration stage of the beam subjected to impact load. However, larger peak values for the internal forces are generated when the subsequent blast load initiates simultaneously with the occurrence of the first peak of impact force. In addition, the vulnerability of different RC beams varied by some important structural parameters including the beam depth, the span length and the configuration of the reinforcements are assessed under a combination of impact and blast loads through a proposed damage index based on the residual flexural capacity of RC beams.